THE HETEROSPOROUS LYCOPODIOPHYTE PLEUROMEIA ROSSICA NEUBURG, 1960 FROM THE TRIASSIC OF THE VOLGA RIVER BASIN (RUSSIA); ORGANOGRAPHY AND RECONSTRUCTION ACCORDING TO THE "WHOLE-PLANT` CONCEPT - Naugolnykh, S. (My University, 2013)
The article deals with the heterosporous lycopodiophyte Pleuromeia rossica Neuburg, 1960 from Lower Triassic deposits of the European part of Russia (the Volga River basin, Yaroslavl region, Rybinsk district). Morphology of stems, rhizophores, reproductive organs (cones, sporophylls) and micro- and megaspores preserved in situ is described in detail. A ‘Whole-Plant’ reconstruction of P. rossica is proposed. Taphonomical observations and palaeoecological considerations are discussed. It is shown that the lycopodiophyte P. rossica grew in semiarid climate nearby waters, where this plant was dominant. Phylogenetically, the Permian genera Viatcheslavia Zalessky and Signacularia Zalessky, the earliest representatives of the family Pleuromeiaceae, should be regarded as direct predecessors of Pleuromeia
Keywords: Lycopodiophyta; Triassic; Pleuromeia; morphology; reconstruction; evolution; Mesozoic::Triassic; Мезозой::Триасовая